Sulfonic acid functionalized ionic liquids for dissolution of metal oxides and solvent extraction of metal ions1. Issue 43 (28th May 2015) - Dupont, David; Raiguel, Stijn; Binnemans, Koen
<x xml:space="preserve">Abstract</x> Sulfonic acid functionalized ionic liquids can dissolve metal oxides and extract metal ions very efficiently.